A preparation method for simultaneously improving the strength and plasticity of niobium microalloyed TRIP steel
Through niobium microalloying and pre-quenching + two-stage heat treatment process, the TRIP steel grains are refined, and its strength and plasticity are improved, which solves the problem of insufficient strength and plasticity of conventional TRIP steel and achieves the simultaneous improvement of high strength and high plasticity.
Patent Information
- Application Number
- CN202410615928.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-17
- Publication Date
- 2025-09-26
- Estimated Expiration
- 2044-05-17
AI Technical Summary
How to further improve the strength and plasticity of conventional TRIP steel to reduce costs and simplify processing difficulty to meet the lightweight and safety requirements of automobiles.
By combining niobium microalloying technology with pre-quenching and two-stage heat treatment processes, and rationally designing the composition and heat treatment parameters, the ferrite grains are refined, the stability of the retained austenite is improved, the phase transformation is delayed, and the TRIP effect is fully exerted.
A low-alloy TRIP steel with a strength-ductility product exceeding 30 GPa·% was produced, with a tensile strength of 876.4 MPa, an elongation of 39.2%, and a strength-ductility product of 34.3 GPa·%, significantly improving the mechanical properties of TRIP steel.
Smart Images

Figure CN118441134B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of material processing, and in particular relates to a preparation method for synchronously improving the strength and plasticity of niobium microalloyed TRIP steel. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance understanding of the overall background of the invention and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to those skilled in the art.
[0003] To achieve vehicle weight reduction, lower fuel consumption, reduce emissions, and improve safety, the use of advanced high-strength steels has become an ideal option for the automotive industry. Transformation-induced plasticity (TRIP) steel, a typical example of advanced high-strength steel, offers both high strength and high plasticity at a low cost. Its use as automotive steel sheet promises to reduce vehicle weight, improve fuel consumption, and enhance vehicle safety, making it a promising candidate for application in the automotive industry. The strength-ductility product of conventional TRIP steels, the first generation of advanced high-strength steels, typically ranges from 15 to 20 GPa∙%. The subsequently developed third generation of advanced high-strength steels, medium-manganese TRIP steels, has seen this product increased to 20 to 40 GPa∙%. However, this product is more expensive than conventional TRIP steels and presents significant production and processing challenges. Therefore, further improving the strength and plasticity of conventional TRIP steels has become a widespread concern within the metal materials community, both domestically and internationally. Summary of the Invention
[0004] In response to the shortcomings of the existing technology, the present invention aims to provide a preparation method for simultaneously improving the strength and ductility of niobium microalloyed TRIP steel. By rationally designing the composition and heat treatment process parameters, a pre-quenching + two-stage heat treatment process is adopted to improve the strength-ductility product of conventional TRIP steel.
[0005] In order to achieve the above object, the technical solution of the present invention is:
[0006] In a first aspect, a preparation method for simultaneously improving the strength and plasticity of niobium microalloyed TRIP steel comprises the following steps:
[0007] S1. Obtaining a steel ingot of niobium microalloyed TRIP steel and performing homogenization heat treatment to obtain a steel billet;
[0008] S2, hot rolling the steel slab in multiple passes, and then air cooling it to room temperature to obtain a hot-rolled steel plate;
[0009] S3, performing multiple cold rolling on the hot-rolled steel sheet with a total reduction of 60-70% to obtain a cold-rolled steel sheet;
[0010] S4, heating the cold-rolled steel plate to 825-900°C, keeping the temperature for 110-130 seconds, and quenching it to room temperature to obtain a quenched steel plate;
[0011] S5. The quenched steel plate is heated to 825±15°C and held for 170-190 seconds. The plate is then quenched into a molten salt at 450±5°C and held for 170-190 seconds. The plate is then air-cooled to room temperature to obtain a niobium microalloyed TRIP steel with high strength and ductility.
[0012] Optionally, in S1, the homogenization heat treatment method includes: keeping the temperature at 1150-1250°C for 1.5-2.5 hours,
[0013] Optionally, in S2, before hot rolling, the steel billet is cut to a set thickness, heated to 1150-1250°C and kept warm for 1.5-2.5 hours, and then hot rolled.
[0014] Optionally, the hot rolling is performed through 5 to 7 passes to continuously hot roll the thickness from 25 to 40 mm to 2 to 4 mm.
[0015] Optionally, in S2, the final rolling temperature of the hot rolling is 850~900℃.
[0016] Optionally, in S3, the hot-rolled steel plate is pickled before cold rolling.
[0017] Optionally, in S3, the pickling method is: pickling with a hydrochloric acid solution with a mass concentration of about 10-15%.
[0018] Optionally, after cold rolling, the thickness of the cold rolled steel sheet is 0.7 to 1.5 mm.
[0019] Optionally, in S4, the cold-rolled steel plate is heated to 825, 850°C, 875°C or 900°C and kept warm for 2 minutes.
[0020] Optionally, in S4, the heating method is: placing the cold-rolled steel plate in molten salt.
[0021] Optionally, in S4, the quenching cooling method is water cooling.
[0022] Optionally, in S5, the heating method is: heating the quenched steel plate and placing it in a molten salt at 825±15°C for 170-190 seconds.
[0023] In a second aspect, the niobium microalloyed TRIP steel prepared by the preparation method for simultaneously improving the strength and ductility of the niobium microalloyed TRIP steel is as follows: C 0.19-0.21%, Mn 1.48-1.52%, Si 1.43-1.45%, Ni 0.79-0.81%, Al 0.16-0.20%, Nb 0.026-0.03%, S 0.003-0.005%, P 0.006-0.008%, and the remainder Fe and unavoidable impurities.
[0024] Optionally, its chemical composition percentage is 0.19% of C, 1.48% of Mn, 1.43% of Si, 0.79% of Ni, 0.16% of Al, 0.026% of Nb, 0.003% of S, 0.007% of P, and the rest is Fe and unavoidable impurities.
[0025] The beneficial effects of the present invention are:
[0026] 1. This invention targets niobium microalloyed TRIP steel, a type of conventional TRIP steel, with low cost and minimal processing difficulty. In a preparation method for simultaneously improving the strength and ductility of niobium microalloyed TRIP steel, the niobium microalloyed TRIP steel is treated using a pre-quenching followed by a two-stage heat treatment process. In conventional TRIP steel microstructures, ferrite grain refinement is a method for dispersing premature stress / strain concentrations in retained austenite. Furthermore, the refined retained austenite exhibits high stability, contributing to the sustained TRIP effect and thus improving the mechanical properties of TRIP steel. Niobium microalloying achieves grain refinement in TRIP steel and a precipitation strengthening effect. Pre-quenching, utilizing a rapid heating, short-term soaking, and rapid cooling technique, can also effectively refine the TRIP steel microstructure. Furthermore, combining microalloying technology with pre-quenching technology is an effective method to utilize dispersed retained austenite to suppress premature stress / strain concentration. It can effectively refine austenite grains, improve the stability of retained austenite, enhance the coordinated deformation ability of each phase, delay the phase transformation of retained austenite, give full play to the TRIP effect, and achieve the effect of simultaneous improvement of strength and plasticity of TRIP steel.
[0027] 2. The composition design of the niobium microalloyed TRIP steel described in this invention incorporates a small amount of the microalloying element Nb in addition to C, Si, and Mn. C primarily improves austenite stability, while Si is insoluble in cementite, providing both enhanced austenite stability and a strong solid solution strengthening effect. The addition of Nb refines the grain size, improving the steel's yield strength and tensile strength. Combining a pre-quenching and two-stage heat treatment process, a low-alloy TRIP steel with a strength-ductility product exceeding 30 GPa∙% was produced, achieving optimal mechanical properties: a tensile strength of 876.4 MPa, an elongation of 39.2%, and a strength-ductility product of 34.3 GPa∙%. This invention clarifies the effects of the pre-quenching process on the microstructure and properties of TRIP steel, which is of great significance for promoting the practical application of TRIP steel. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The accompanying drawings, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0029] Figure 1 Schematic diagram of the pre-quenching + two-stage heat treatment process in a specific embodiment of the present invention;
[0030] Figure 2 is a scanning electron microscope tissue diagram of a sample obtained in a specific embodiment of the present invention;
[0031] Figure 3 is an X-ray diffraction pattern of a sample before stretching obtained in a specific embodiment of the present invention;
[0032] Figure 4 is a post-fraction X-ray diffraction pattern of a sample obtained in a specific embodiment of the present invention;
[0033] Figure 5 The engineering stress-strain curve of the sample obtained in the specific embodiment of the present invention is shown in FIG. DETAILED DESCRIPTION
[0034] It should be noted that the following detailed descriptions are exemplary and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the present invention belongs.
[0035] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is intended to include the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, they indicate the presence of features, steps, operations, devices, components and / or combinations thereof.
[0036] In the following embodiments, the rolling mill used is a two-roll rolling mill.
[0037] In the following examples, pickling was performed using a hydrochloric acid solution having a mass concentration of 10%.
[0038] In the following embodiments, the pre-quenching + two-stage heat treatment process adopts a well-type salt bath furnace.
[0039] Example 1
[0040] A preparation method for simultaneously improving the strength and plasticity of niobium microalloyed TRIP steel comprises the following steps:
[0041] S1. Smelt according to the set chemical composition and cast into a 50 kg ingot. After the ingot is homogenized and heat treated at 1200 ° C for 2 hours, it is cast into a steel billet with a cross-sectional area of 100 mm × 30 mm and air-cooled to room temperature.
[0042] After testing, the mass percentage content of each element is C: 0.19%, Mn: 1.48%, Si: 1.43%, Ni:0.79%, Al: 0.16%, Nb: 0.026%, S: 0.003%, P: 0.007%, and the rest are Fe and inevitable impurities.
[0043] S2. Cut the steel billet obtained in step S1 into small square samples with a size of 100 mm × 100 mm × 30 mm, heat them to 1200°C and keep them warm for 2 h, and then hot-roll the small square samples through 6 passes to continuously reduce the thickness from 30 mm to 3 mm (the final rolling temperature is 870°C). Finally, air-cool them to room temperature to obtain hot-rolled steel plates.
[0044] S3. The hot-rolled steel sheet obtained in step S2 is pickled, and then the experimental steel is cold-rolled in multiple passes at room temperature to reduce the thickness from 3 mm to 1 mm with a total reduction of 66%, thereby obtaining a cold-rolled steel sheet.
[0045] S4, such as Figure 1 As shown, the cold-rolled steel plate obtained in S3 is placed in sodium chloride salt at 825 ° C for 2 min, and then quenched to room temperature. The quenching cooling method is water cooling to obtain a quenched steel plate.
[0046] S5, such as Figure 1 As shown in Figure 1, the quenched steel plate in S4 was placed in sodium chloride salt at 825 °C for 3 minutes, then quenched into nitrate (a mixture of sodium nitrite and potassium nitrate) at 450 °C for 3 minutes, and then air-cooled to room temperature to obtain niobium microalloyed TRIP steel with high strength and plasticity.
[0047] Among them, step S4 is a pre-quenching process, and step S5 is a two-stage heat treatment process; S4 and S5 are collectively referred to as: pre-quenching + two-stage heat treatment process.
[0048] Figure 1 In the figure, WQ refers to the water cooling process, AC refers to the air cooling process, the Ac1 temperature line refers to the starting temperature of the transformation of pearlite to austenite during heating; the Ac3 temperature line refers to the final temperature of the transformation of ferrite to austenite during heating; the Ms temperature line refers to the starting temperature of the transformation of austenite to martensite during cooling.
[0049] Example 2
[0050] A preparation method for simultaneously improving the strength and plasticity of niobium microalloyed TRIP steel, which differs from Example 1 in that:
[0051] In step S4, Figure 1 As shown, the cold-rolled steel plate obtained in S3 is placed in sodium chloride salt at 850°C for 2 minutes, and then quenched to room temperature. The quenching cooling method is water cooling to obtain a quenched steel plate.
[0052] Example 3
[0053] A preparation method for simultaneously improving the strength and plasticity of niobium microalloyed TRIP steel, which differs from Example 1 in that:
[0054] In step S4, Figure 1 As shown, the cold-rolled steel plate obtained in S3 is placed in sodium chloride salt at 875°C for 2 minutes, and then quenched to room temperature. The quenching cooling method is water cooling to obtain a quenched steel plate.
[0055] Example 4
[0056] A preparation method for simultaneously improving the strength and plasticity of niobium microalloyed TRIP steel, which differs from Example 1 in that:
[0057] In step S4, Figure 1 As shown, the cold-rolled steel plate obtained in S3 is placed in sodium chloride salt at 900°C for 2 minutes, and then quenched to room temperature. The quenching cooling method is water cooling to obtain a quenched steel plate.
[0058] Comparative Example
[0059] A method for preparing niobium microalloyed TRIP steel comprises the following steps:
[0060] S1. Smelt according to the set chemical composition and cast into a 50kg ingot. After the ingot is kept at 1200℃ for 2h, it is cast into a square billet with a cross-sectional area of 100mm×30mm and air-cooled to room temperature;
[0061] After testing, the mass percentage content of each element is C: 0.19%, Mn: 1.48%, Si: 1.43%, Ni:0.79%, Al: 0.16%, Nb: 0.026%, S: 0.003%, P: 0.007%, and the rest is Fe and inevitable impurities.
[0062] S2. Cut the square billet obtained in step S1 into small square samples with a size of 100 mm × 100 mm × 30 mm, heat them to 1200°C and keep them warm for 2 h, and then hot-roll the small square samples through 6 passes. The experimental steel is continuously hot-rolled from a thickness of 30 mm to a thickness of 3 mm (the final rolling temperature is 870°C), and finally air-cooled to room temperature to obtain a hot-rolled steel plate.
[0063] S3. Pickling the hot-rolled steel plate obtained in step S2, and then cold-rolling the test steel in multiple passes at room temperature, cold-rolling the test steel plate from 3 mm to 1 mm with a total reduction of 66%, to obtain a cold-rolled steel plate.
[0064] S4. The cold-rolled steel sheet obtained in S3 is placed in chloride salt at 825°C for 3 minutes, then quenched in nitrate (a mixture of sodium nitrite and potassium nitrate) at 450°C for 3 minutes, and finally air-cooled to room temperature to obtain niobium microalloyed TRIP steel.
[0065] The difference from Examples 1 to 4 is that after the cold-rolled steel sheet is obtained in S3, the pre-quenching and two-stage heat treatment processes are not performed, but the pre-quenching is canceled and the two-stage heat treatment process is directly performed.
[0066] Performance testing
[0067] The heat-treated steel sheets obtained in Examples 1 to 4 and the comparative example were prepared into metallographic specimens and their microstructures were observed under a scanning electron microscope. Figure 2 As shown; the equipment used is Nova-NanoSEM450 scanning electron microscope.
[0068] The metallographic specimen preparation method includes: first, grinding the specimen to a smooth mirror surface using coarse to fine sandpaper, then electropolishing it using an electrolytic polisher. The polishing solution is a mixture of 900 mL of anhydrous ethanol and 60 mL of perchloric acid. The polishing voltage is 25V and the polishing time is 30 seconds. After polishing, the specimen is immediately rinsed with anhydrous ethanol and blown dry with a hair dryer. Finally, the polished specimen is etched with 4% nitric acid for 10-15 seconds. After etching, it is immediately rinsed with anhydrous ethanol and blown dry.
[0069] Figure 2 The scanning electron microscope organization diagrams of each sample after pre-quenching at different temperatures and two-stage heat treatment are shown. Figure 2 (a) represents a comparative example; Figure 2 (b) represents Example 1; Figure 2 (c) represents Example 2; Figure 2 (d) represents Example 3; Figure 2 (e) represents Example 4. Figure 2 It can be seen that after heat treatment with different processes, the microstructure of each sample is composed of ferrite, bainite and retained austenite. Figure 2 In the figure, ferrite is marked as "F" and has a dark grey concave polygonal shape; bainite is marked as "B" and has a raised block or island shape; retained austenite is marked as "RA" and has a bright white granular or film shape. The software measured that the average ferrite grain size of the comparative sample is 4.2 μm ( Figure 2 (a)), the average ferrite grain size of Example 1 is 3.7 μm ( Figure 2 (b)), the average ferrite grain size of Example 2 is 3.4 μm ( Figure 2 (c)), the average ferrite grain size of Example 3 is 3.1 μm ( Figure 2 (d)), the average ferrite grain size of Example 4 is 3.3 μm ( Figure 2 (e)).
[0070] The heat-treated steel sheets obtained in Examples 1 to 4 and the comparative example were prepared into X-ray diffraction samples and subjected to X-ray diffraction testing. The results are as follows: Figure 3 As shown; the equipment used is German Bruker D8 X-ray diffractometer.
[0071] The preparation method of X-ray diffraction samples includes: first grinding the sample surface with sandpaper, then polishing the polished sample with an electrolytic polishing machine, wherein the polishing liquid is a mixture of 900 mL of anhydrous ethanol and 60 mL of perchloric acid, the polishing voltage is 25 V, and the polishing time is 30 s. After polishing, rinse with alcohol and blow dry.
[0072] Depend on Figure 3It can be seen that after pre-quenching at different temperatures + two-stage heat treatment, the microstructure of each sample is composed of ferrite / bainite in the body-centered cubic (BCC) phase and retained austenite in the face-centered cubic (FCC) phase; among them, the volume fractions of retained austenite in the comparative example sample, the sample in Example 1, the sample in Example 2, the sample in Example 3 and the sample in Example 4 are 12.8%, 13.5%, 14.3%, 15.6% and 14.7%, respectively.
[0073] The heat-treated steel plates obtained in Examples 1-4 and the comparative example were subjected to room-temperature uniaxial tensile testing to obtain engineering stress-strain curves, measure elongation, and calculate the strength-ductility product. The equipment used was an Instron electronic universal testing machine, model INSTRON 2382. During the room-temperature uniaxial tensile testing, the tensile specimens were polished with sandpaper before being stretched at a rate of 0.6 mm / min until fracture. The entire process was automatically controlled by a computer program.
[0074] The fractured sample obtained by uniaxial stretching was subjected to X-ray diffraction, and the results were as follows: Figure 4 As shown, Figure 4 The comparative examples and embodiments in the present invention are expressed in the same way as Figure 3 same.
[0075] Figure 4 and Figure 3 By comparison, it can be seen that after tensile deformation, the peak intensity of the γ phase representing the retained austenite in each sample is greatly reduced, which indicates that the volume fraction of the retained austenite in each sample is greatly reduced. This indicates that a significant TRIP effect has occurred in each sample during the tensile deformation process, and most of the retained austenite has undergone phase transformation and transformed into martensite.
[0076] Figure 5 The engineering stress-strain curves of each sample after pre-quenching at different temperatures + two-stage heat treatment are shown in Table 1. Figure 5 As shown in Table 1, the yield strength, tensile strength, elongation, and strength-ductility product of the samples in Examples 1-4 all increased after pre-quenching compared to the comparative example. As the pre-quenching temperature increased from 825°C to 875°C, the yield strength increased from 595.2 MPa to 628.1 MPa; the tensile strength slightly increased from 870.2 MPa to 876.4 MPa; the elongation increased from 36.1% to 39.2%; and the strength-ductility product increased from 31.4 GPa∙% to 34.3 GPa∙%. When the pre-quenching temperature reached 900°C, the yield strength, tensile strength, elongation, and strength-ductility product of the sample in Example 4 all decreased compared to those in Example 3, reaching 615.2 MPa, 864.8 MPa, 35.2%, and 30.4 GPa∙%, respectively.
[0077] The mechanical properties of Examples 1 to 4 and the comparative example are summarized and statistically analyzed, and the data results are shown in Table 1.
[0078] Table 1
[0079]
[0080] As can be seen from Table 1, all properties of the examples are superior to those of the comparative examples, indicating that the method of the present invention can produce products with higher strength-ductility ratios using the chemical composition of conventional TRIP steel, and that all mechanical properties are improved. Among them, the sample obtained in Example 3 has the best performance.
[0081] The foregoing description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art will readily appreciate that various modifications and variations of the present invention are possible. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention are intended to be within the scope of protection of the present invention.
Claims
1. A preparation method for simultaneously improving the strength and plasticity of niobium microalloyed TRIP steel, characterized by the following steps: include: S1. Obtaining a steel ingot of niobium microalloyed TRIP steel and performing homogenization heat treatment to obtain a steel billet; S2, hot rolling the steel slab in multiple passes, and then air cooling it to room temperature to obtain a hot-rolled steel plate; S3, performing multiple cold rolling on the hot-rolled steel sheet with a total reduction ratio of 60-70% to obtain a cold-rolled steel sheet; S4, heating the cold-rolled steel plate to 825-900°C, keeping the temperature for 110-130 seconds, and quenching it to room temperature to obtain a quenched steel plate; S5. The quenched steel plate is heated to 825±15°C and kept at this temperature for 170-190 seconds. The steel plate is then quenched into a molten salt at 450±5°C and kept at this temperature for 170-190 seconds. The steel plate is then air-cooled to room temperature to obtain a niobium microalloyed TRIP steel with high strength and ductility.
2. The method for simultaneously improving the strength and plasticity of niobium microalloyed TRIP steel according to claim 1, wherein: In S1, the homogenization heat treatment method includes: keeping the temperature at 1150-1250°C for 1.5-2.5 hours.
3. The method for simultaneously improving the strength and ductility of niobium microalloyed TRIP steel according to claim 2, wherein, in S2, before hot rolling, the steel billet is cut to a set thickness, heated to 1150-1250°C and held at that temperature for 1.5-2.5 hours, and then hot rolled.
4. The method for simultaneously improving the strength and plasticity of niobium microalloyed TRIP steel according to claim 3, wherein: The final rolling temperature of hot rolling is 850~900℃.
5. The method for simultaneously improving the strength and plasticity of niobium microalloyed TRIP steel according to claim 3, wherein: After 5 to 7 hot rolling passes, the thickness is continuously hot rolled from 25 to 40 mm to 2 to 4 mm.
6. The method for simultaneously improving the strength and plasticity of niobium microalloyed TRIP steel according to claim 5, wherein: Continuously hot rolled to 3 mm.
7. The method for simultaneously improving the strength and plasticity of niobium microalloyed TRIP steel according to claim 1, wherein: In S3, the hot rolled steel sheet is pickled before cold rolling.
8. The method for simultaneously improving the strength and plasticity of niobium microalloyed TRIP steel according to claim 7, wherein: The pickling method is: pickling with a hydrochloric acid solution with a mass concentration of 10~15%.
9. The method for simultaneously improving the strength and plasticity of niobium microalloyed TRIP steel according to claim 7, wherein: After cold rolling, the thickness of the cold rolled steel sheet is 0.7~1.5 mm.
10. The method for simultaneously improving the strength and plasticity of niobium microalloyed TRIP steel according to claim 9, wherein: After cold rolling, the thickness of the cold rolled steel sheet is 1 mm.
11. The method for simultaneously improving the strength and plasticity of niobium microalloyed TRIP steel according to claim 5, wherein: In S4, the cold-rolled steel plate is heated to 850°C or 875°C and kept at this temperature for 110-130 seconds.
12. The method for simultaneously improving the strength and plasticity of niobium microalloyed TRIP steel according to claim 11, wherein: The heating method is: placing the cold-rolled steel plate in molten salt.
13. The method for simultaneously improving the strength and plasticity of niobium microalloyed TRIP steel according to claim 11, wherein: The cooling method for quenching is water cooling.
14. The method for simultaneously improving the strength and plasticity of niobium microalloyed TRIP steel according to claim 11, wherein: In S4, the cold-rolled steel plate is heated to 875°C and kept at this temperature for 2 minutes.
15. The method for simultaneously improving the strength and plasticity of niobium microalloyed TRIP steel according to claim 1, wherein: In S5, the quenched steel plate is placed in molten salt and heated to 825±15℃ and kept at this temperature for 170~190s.
16. A niobium microalloyed TRIP steel with high strength-ductility product produced by the method for simultaneously improving the strength and ductility of niobium microalloyed TRIP steel according to any one of claims 1 to 15, wherein: The mass percentages of its chemical composition are: C 0.19~0.21%, Mn 1.48~1.52%, Si 1.43~1.45%, Ni 0.79~0.81%, Al 0.16~0.20%, Nb 0.026~0.03%, S 0.003~0.005%, P 0.006~0.008%, and the rest are Fe and unavoidable impurities.
17. The high strength-ductility niobium microalloyed TRIP steel according to claim 16, wherein: Its chemical composition percentage is C 0.19%, Mn 1.48%, Si 1.43%, Ni 0.79%, Al 0.16%, Nb 0.026%, S 0.003%, P 0.007%, and the rest is Fe and unavoidable impurities.
Citation Information
Patent Citations
Thermal treatment method for low-carbon microalloying cold-rolled TRIP980 steel with high product of strength and elongation
CN109182923A
1180 MPa-grade ultrahigh-strength low-cost cold-rolled quenched partition steel and manufacturing method thereof
CN110093564A